DEVELOPMENT OF ARABIC LANGUAGE IN BUSINESS AND INDUSTRY AT ARABIC EDUCATION DEPARTMENT IAIN KEDIRI - Fahraini, Sovia; Muhammad Fikri Almaliki; Ahmad Rifa’i; Moh Sholeh Afyuddin (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
Arabic is the second international language in the world and is the language for the source of Muslim law, so it is studiedfrom elementary school to university. However, many Arabic language education scholars experience difficulty in generating financial returns and lack creativity. If it continues, many graduates will be unemployed due to the lack of job opportunities. Therefore, Indonesia implements the Merdeka Belajar Kampus Merdeka (MBKM) curriculum as a solution in higher education, but this is still a transition from the Kerangka Kualifikasi Nasional Indonesia (KKNI) curriculum. This study aims to understand the role of the Arabic language study program at IAIN Kediri in developing Arabic in the era of business and industry. This research method uses a descriptive qualitative approach through questionnaires, interviews, and observations to obtain valid data. The results showed that the Entrepreneurship Course Program (KWU) in the Arabic language education study program at the Kediri State Islamic Institute provided maximum results in developing entrepreneurial abilities according to student expectations. This research provides an overview of the implementation of Arabic language development in business and industry through marketing and management in the fields of translation, tutoring, tourism and language seminars with the hope that it can be implemented into business and industry in the future.